Ultra‐small, Uniform, and Single bcc‐Phased FexCo1‐x/Graphitic Shell Nanocrystals for T1 Magnetic Resonance Imaging Contrast Agents. Issue 1 (14th November 2012) - Choi, In Ae; Li, Yan; Kim, Da Jeong; Pal, Mou; Cho, Jee‐Hyun; Lee, Kyujoon; Jung, Myung‐Hwa; Lee, Chulhyun; Seo, Won Seok
Abstract We have synthesized ultra‐small and uniform FexCo1‐x/graphitic carbon shell (FexCo1‐x/GC) nanocrystals (x=0.13, 0.36, 0.42, 0.50, 0.56, and 0.62, respectively) with average diameters of <4 nm by thermal decomposition of metal precursors in approximately 60 nm MCM‐41 and methane CVD. The composition of the FexCo1‐x/GC nanocrystals can be tuned by changing the Fe:Co ratios of the metal precursors. The FexCo1‐x/GC nanocrystals show superparamagnetic properties at room temperature. The Fe0.50Co0.50/GC, Fe0.56Co0.44/GC, and Fe0.62Co0.38/GC nanocrystals have a single bcc FeCo structure, whereas the Fe0.13Co0.87/GC, Fe0.36Co0.64/GC, and Fe0.42Co0.58/GC nanocrystals have a mixed structure of bcc FeCo and fcc Co. The single bcc‐phased FexCo1‐x/GC nanocrystals functionalized with phospholipid–poly(ethylene glycol) (PL–PEG) in phosphate buffered saline (PBS) are demonstrated to be excellent T1 MRI contrast agents.